Modeling of tsunami run-up using terrain model data based on photogrammetry processing product (case study at Way Muli Village, Rajabasa, South Lampung) - Muhammad Ulin Nuha; Naufal Hilmi; Adhitya Erlangga Pamungkas; Chantika Dwi Novita; Adam Irwansyah Fauzi; Rizky Ahmad Yudanegara; Aulia Try Atmojo (Elipsoida : Jurnal Geodesi dan Geomatika, 2021)
Photogrammetry has become a trend in large-scale mapping today. The ability to produce large-scale geospatial products in a relatively short time and low cost is very beneficial for mapping. The ability of high temporal and spatial resolution also makes photogrammetry used in the disaster mapping process. In this study, the DEM approach from photogrammetry was used for input data in tsunami run-up modeling activities in Way Muli Village. High temporal and spatial capabilities are utilized for the production of surface roughness and elevation which are key parameters for rigorous inundation modeling. The modeled inundation results show that the run-up limit achieved in residential areas is on the main road with a maximum distance of inundation from the shoreline is an average of 80 m. The results obtained can be used by the village government to preparedness in dealing with the tsunami.